Creation of Educational Materials Centered on Audio-Visual Elements From a Neuroscientific Standpoint: Serving as a Foundation for An Autonomous Curriculum Ethos Within Vocational Schools - Mohammad Jailani (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Drawing from Nadiem Makarim's scholarly address, which emphasized the imperative for teachers to possess creativity in their instructional methods, he further emphasized that information technology and all fields of knowledge are rapidly advancing. Hence, educators in the modern era need to exhibit adept teaching techniques. However, the reality is that a considerable number of teachers lack innovation in their approaches. Traditional teaching methods are often employed, leading to limited improvements in student learning outcomes. The objective of this research was to design brain-based learning tools for use at SMK Muhammadiyah 3 Yogyakarta. The research methodology employed in this study was research and development (R&D). The research participants encompassed both teachers and students. Data collection methods included interviews, observations, and documentation. Data validity was assured through triangulation. Data analysis followed the Miles and Huberman model, encompassing data reduction, data presentation, and the drawing of conclusions or the verification of data. The findings of this investigation affirm that learning media is highly effective in enhancing student learning results. The evaluation by media experts yielded an average score of 5.0 (expert 1) and 5.0 (expert 2) with the assessment of